Occurrence of Bacterial Conjunctivitis and Viral Conjunctivitis in Pakistan - Muhammad Usman Arshad, Sohail Zia, Aunaza Maqbool, Rabia Sharif Bhatti, Masud-Ul-Hassan, Muhammad Sajid Munir, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To identify the prevalence of bacterial and viral conjunctivitis. Study design: Prospective study. Place and Duration of Study: Department of Ophthalmology, Pakistan Railways Hospital, Islamic International Medical College, Rawalpindi from 1st April 2021 to 30th September 2021. Methodology: Fifty conjunctivitis patients enrolled within age of 14-29 years. Clinical examination, slit lamp test and lab testing separated cases as viral or bacterial conjunctivitis. Polymerase chain reaction post culturing was sued in viral conjunctivitis cases while Kirby-Baur disc diffusion assay was sued in bacterial conjunctivitis confirmation. Results: There were 91.17% patients with viral conjunctivitis in age of 24-29 years and 62.5% patients with bacterial conjunctivitis within 14-18 years. The odds ratio value between the male and female gender showed a significant difference between both genders with 95% confidence interval with higher female frequency in both. Coronavirus cases were highest with 52.9% while cases of Micrococciwere highest as 37.5% with conjunctivitis. Conclusion: Viral conjunctivitis was more common in general cases due to recent covid-19 infection followed by Micrococci bacterial conjunctivitis.